A MAGNITUDE INDEPENDENT SPACE-TIME EARTHQUAKE CLUSTERING ALGORITHM (MISTIC) - Leptokaropoulos, K.M.; Gkarlaouni, C.G (Bulletin of the Geological Society of Greece, 2016)
This paper introduces "MISTIC", a magnitude independent program for the analysis of spatio-temporal earthquake clustering, developed on the basis of a simple clustering algorithm which is implemented in Matlab. The method is conceptually based upon the comparison of the inter-event time and the epicentral/hypocentral distance between subsequent events, with pre-defined values, without any magnitude constraints. The code identifies spatial concentrations of the seismic activity which exhibit enhanced occurrence rates, significantly higher than the average or background seismicity rates. The visualization tools provided by the program’s interface, enable the user to directly test and control the whole process. The calculations are performed fast even for relatively large catalogs. The description of the algorithm along with some examples are presented in this work. Moreover, an application in the local microseismicity catalog for Samos-Karaburun area, in eastern Aegean Sea, is also demonstrated. The identified clusters which are extracted from the analysis, exhibit special characteristics varying from a typical mainshock/ aftershock behaviour to a swarm-like activity. Further testing and improvement of the source code are scheduled in order to constitute "MISTIC" a fast and useful tool for seismic cluster analysis.